PENGARUH RISIKO BISNIS, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, KEBIJAKAN DIVIDEN, DAN STRUKTUR ASET TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017–2020 - Timotius Valentino Purba; Ninta Katharina (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted in the manufacturing industry where it is known that if a manufacturing company is not careful in managing its assets and dividend policy, it can affect stock prices and investor confidence in the issuer of the company. The purpose of this research is to find out and analyze whether partially and simultaneously independent variables affect stock prices. The research approach used is deductive, the type of research is quantitative and descriptive. The population in this study are all manufacturing companies listed on the Stock Exchange from 2017 to 2020. The population in this study amounted to 193 companies and there were 16 companies that met the criteria. The sampling technique in this study is based on purposive sampling. The results of this study partially show that business risk, sales growth, and asset structure have no effect on stock prices of manufacturing companies listed on the Indonesia Stock Exchange in 2017–2020 while company size and dividend policy have a partial impact on the stock prices of manufacturing companies listed on the Indonesia Stock Exchange in 2017–2020. Simultaneously, business risk, company size, sales growth, dividend policy, and asset structure affect the stock prices of manufacturing companies listed on the Indonesia Stock Exchange in 2017–2020 with an Adjusted R Square value of 52.7% of stock price variations which can be explained by 5 independent variables and the remaining 47.3% is explained by other variables, such as profitability, liquidity, and others.